Recent development on optimization of bio-cementation for soil stabilization and wind erosion control - Jia He; Yang Liu; Lingxiao Liu; Boyang Yan; Liangliang Li; Hao Meng; Lei Hang; Yongshuai Qi; Min Wu; Yufeng Gao (Biogeotechnics)
This paper reviews and analyzes recent research development on bio-cementation for soil stabilization and wind erosion control. Bio-cement is a type of cementitious materials by adopting natural biological processes for geotechnical and construction applications. Bio-cementation is usually achieved through microbially- or enzyme-induced carbonate precipitation (MICP or EICP). The use of soybean urease can be a cost-effective solution for carbonate precipitation and bio-cementation, which is named SICP. The produced calcium carbonate can cement soil particles and bring considerable strength improvement to soils. In this paper, the mechanisms and recent development on the technology optimization are reviewed first. The optimization of bio-cementation involves 1) altering the treatment materials and procedures such as using lysed cells, low pH, the salting-out technique; and 2) using cheap and waste materials for bio-cement treatment and bacterial cultivation. The objectives are to improve treatment uniformity and efficiency, use bio-cement in more scenarios such as fine-grain soils, and reduce costs and environmental impacts, etc. Studies on the mechanical behaviour and wind erosion performances of bio-cemented soil show that the wind erosion resistance can be improved significantly through the bio-cement treatment. In addition, the use of optimized method and additives such as xanthan gum and fibers can further enhance the strength, treatment uniformity or ductility of the bio-cemented soils. Attention should be paid to wind forces with saltating particles which have much stronger destructive effect than pure wind, which should be considered in laboratory tests. Field studies indicate that bio-cement can improve soil surface strength and wind erosion resistances effectively. Besides, local plants can germinate and grow on bio-cemented soil ground with low-concentration treatments.